Writing a (trans)creative dance: (im)possible articulations in the education of a kinetic-icon body that writes a (trans)creative dance (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article explores the perspective of the kinetic-icon body in educational and (trans)creative action in the process of derivation or hyper-artistic practice from one language into another. The expanded semiotic analysis methodology starts with a critical reading of excerpts from the ballet Reticências (2023) performed by UFPR´s Téssera Companhia de Dança, adapted from the play Vestido de Noiva written by Nelson Rodrigues in 1941. Drawing mainly on the ideas of Charles S. Peirce, Gérard Genette, and Haroldo de Campos, the relationships between the body and writing in the contemporary scene are exponentiated to highlight the (im)possible articulations between the theatrical text and the word embodied or (trans)created in a dance scene.
Keywords: language; dance; transcreation; kinetic-icon body